His gift, my story : Kim's musical journey [compact disc] - Collingsworth, Kim (Gaither gospel series., 2026)
Virtuoso pianist and matriarch of the celebrated Collingsworth Family, Kim Collingsworth showcases her unique, energetic blend of classical-meets-gospel piano talents through this solo concert recording captured at the elegant Fisher Center at Belmont in Nashville, TN. Featuring special guests such as Dino Kartsonakis and Lanny Wolfe, Kim documents her life through song and testimony with thrilling performances of gospel, patriotic and pop classics for a night of beauty and worship.